U.S. intervention and regime change in Nicaragua - Solaún, Mauricio (University of Nebraska Press, 2005)
As President Carter's ambassador to Nicaragua from l977-1979, Mauricio Solaún witnessed a critical moment in Central American history. In U.S. Intervention and Regime Change in Nicaragua, Solaún outlines the role of U.S. foreign policy during the Carter administration and explains how this policy with respect to the Nicaraguan Revolution of 1979 not only failed but helped impede the institutionalization of democracy there. Solaún explores the mechanisms that kept Somoza's poorly legitimized regime in power for decades, making it the most enduring Latin American authoritarian regime of the twentieth century. Solaún argues that continual shifts in U.S. international policy have been made in response to previous policies that failed to produce U.S.- friendly international environments. His historical survey of these policy shifts provides a window on the working of U.S. diplomacy and lessons for future policy-making.